Budżetowanie kosztów jako instrument zarządzania kosztami w zakładzie ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of this paper is to present cost budgeting as the one of cost management' instruments in an insurance company. These financial institutions are very specific because they have different costs calculation methods, different character of product, and different character of activity. The range of cost management in insurance companies contains strategic and operative parts of management process. One of the most important instruments of this process is cost budgeting whose the main aim is to plan results of technical and investment activities. There are two ways of budgeting in an insurance company. The first way is traditional cost budgeting with elements of variable costing. The second way of cost budgeting is activity based budgeting. The Polish insurance companies could have problems with competitive institutions from European insurance market so that cost management and cost budgeting should be the most important instruments of management process. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 16-24